2000
DOI: 10.1159/000053999
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccination against La Crosse Virus

Abstract: For the development of effective conventional vaccines or DNA vaccines against viruses, the availability of suitable animal models is an essential prerequisite. For many recently emerging zoonotic viruses, suitable animal models are still missing. We have established a novel small animal model for DNA vaccines using mice lacking a functional interferon-α/β receptor (IFNAR-1). IFNAR-1-deficient mice are highly susceptible to many different viruses despite their ability to mount a normal humoral and cellular imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In previous studies, deficiency in Ifnar1 increased susceptibility to LACV in adult mice (10). Similarly, infection of Irf3…”
Section: Irf3mentioning
confidence: 72%
See 2 more Smart Citations
“…In previous studies, deficiency in Ifnar1 increased susceptibility to LACV in adult mice (10). Similarly, infection of Irf3…”
Section: Irf3mentioning
confidence: 72%
“…Infected weanling mice develop neurological disease with high CNS viral titers (8,9). In contrast, adult mice do not generally show signs of neurological disease and have minimal titers of virus in the CNS (9)(10)(11). However, adult mice develop neurological disease when LACV is administered intracerebrally (i.c.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Type-I interferon responses in mice were shown to be crucial for LACV clearance and reduction of LACV-induced neurological diseases [14,47,48]. In the LACV stimulation experiments using Mincle −/− , CARD9 −/− , and WT DCs, a decreased type-I interferon-β (IFN-β) production could be detected only in CARD9 −/− DCs by luminescence IFN-β ELISA (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Because LACV infects and causes encephalitis only in newborn mice and mice become resistant to infection as adults, there is a need to develop new animal models to test potential vaccines and antiviral drugs. Recently, there have been attempts to develop a DNA vaccine against LACV by using interferon type I (IFNAR-1) knockout mice (Schuh et al, 1999;Pavlovic et al, 2000). Previous studies showed that IFNAR-1 knockout mice are highly susceptible to infections with LACV and develop encephalitis regardless of their age (Muller et al, 1994;Hefti et al, 1999).…”
Section: Bunyaviridaementioning
confidence: 99%